Tantangan Penegakan Hukum dalam Pembuktian Tindak Pidana Terorisme di Indonesia - Servasius Edwin Telaumbanua; Yasmirah Mandasari Saragih; Bonar Yudhistira; Elisabeth Saragih; Tengku Ikhsan Ansyari Husni (Lembaga Pengembangan Kinerja Dosen, 2025)
Terrorism is an extraordinary crime that poses a serious threat to both national and international security. Law enforcement efforts against such crimes face complex challenges, particularly in the evidentiary process. The process of proving terrorism-related offenses involves not only formal legal procedures but also substantive aspects, including the role of intelligence, the use of information technology, and the protection of human rights. This study aims to comprehensively examine the obstacles encountered by law enforcement authorities in proving acts of terrorism and to propose normative and practical solutions based on the development of national criminal law. The research employs a normative juridical approach, utilizing secondary data sourced from legislation, legal literature, and scholarly journals. The findings highlight the need for a reformulation of evidentiary approaches that are more adaptive to modern terrorism modus operandi, as well as the importance of enhancing cross-sectoral and international cooperation in the enforcement of anti-terrorism laws in Indonesia.